Introduction - Bulan, Ramy (Journal of Malaysian and Comparative Law, 1999)
The papers compiled in this volume are selected papers from the proceedings of an International Workship on Estoppel jointly organised by the Faculties of Law, Universities of Hong Kong, International Islamic University, University Kebangsaan Malaysia and University of Malaya and hosted by the Faculty of Law, University of Malaya on 23-25 August 1999. The workshop was a follow-up of an International Workshop on the New Equity held in Hong Kong in September 1998, organised by the University of Hong Kong. The discussinos focused on the case of Union Eagle Ltd v Golden Achivement Ltd.